2018
DOI: 10.1111/cge.13198
|View full text |Cite
|
Sign up to set email alerts
|

De novo variants in KLF7 are a potential novel cause of developmental delay/intellectual disability, neuromuscular and psychiatric symptoms

Abstract: Due to small numbers of reported patients with pathogenic variants in single genes, the phenotypic spectrum associated with genes causing neurodevelopmental disorders such as intellectual disability (ID) and autism spectrum disorder is expanding. Among these genes is KLF7 (Krüppel‐like factor 7), which is located at 2q33.3 and has been implicated in several developmental processes. KLF7 has been proposed to be a candidate gene for the phenotype of autism features seen in patients with a 2q33.3q34 deletion. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…5). Two of the transcription factors that were regulated in opposite directions ( NR3C1 and klf7b ) have been implicated with social behavior in other studies (the glucocorticoid receptor NR3C1 and psychosocial stress during pregnancy 39 ; klf7b and austim spectrum disorder 40 ). These patterns suggest that for some genes, different salient experiences—providing paternal care and territorial aggression—trigger opposite gene regulatory responses.
Fig.
…”
Section: Resultsmentioning
confidence: 92%
“…5). Two of the transcription factors that were regulated in opposite directions ( NR3C1 and klf7b ) have been implicated with social behavior in other studies (the glucocorticoid receptor NR3C1 and psychosocial stress during pregnancy 39 ; klf7b and austim spectrum disorder 40 ). These patterns suggest that for some genes, different salient experiences—providing paternal care and territorial aggression—trigger opposite gene regulatory responses.
Fig.
…”
Section: Resultsmentioning
confidence: 92%
“…In addition, klf7-deficient mice showed a poorer nest-building ability, which suggest a social interaction defect ( Supplementary Figure S4E ) [ 33 , 34 ]. Studies have shown that individuals with klf7 mutations are associated with intellectual disability [ 22 ]. In a novel object recognition experiment, both WT and klf7 +/− mice similarly recognized the novel object ( Supplementary Figure S4F,G ), while klf7 −/− mice showed a significantly decreased interaction time ratio (time spent interacting with the novel object/time spent interacting with the familiar object) ( Supplementary Figure S4F ) and a slightly decreased interaction frequency ratio (number of interactions with the novel object/number of interactions with the familiar object) ( Supplementary Figure S4G ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies indicate a possible relationship between loss of klf7 and ASD. In addition, another study reported four unrelated individuals with de novo mutations in klf7 accompanied by ASD-related developmental delay/intellectual disability (DD/ID) and neuromuscular and psychiatric complications [ 22 ]. Owing to the transcriptional regulation activity and strong expression of klf7 in the central nervous systems [ 23 ], klf7 may be a causal gene in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Four unrelated individuals with de novo inactivating mutations in the Krüppel-like factor 7 (KLF7) gene exhibited autistic features along with ID (141). KLF7 is a poly-ZNF, and is essential for neurogenesis and is involved in neuronal differentiation and morphogenesis (141,142). Klf7knockout mice showed impaired axon projection in several brain regions including the cerebral cortex and hippocampus, and exhibited reduced dendritic branching in hippocampus (142).…”
Section: Involvement Of C 2 H 2 -Znfs In Asds and Down Syndromementioning
confidence: 99%